Analisis Pandemi Covid-19 Dalam Presfektif Collective Action (Studi Kasus: Kecamatan Cariu Kabupaten Bogor) - Anton Hilman; Ramadhan Pancasilawan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
In the midst of the Covid-19 pandemic, many people are affected by health, economic and social aspects. With the existence of a government policy regarding large-scale social restrictions to break the chain of the virus but it creates new problems in the community. Starting from the existing problems, social actions or social activities can help overcome covid-19. Collective actions taken by the community in the midst of the Covid-19 pandemic are small things that can help overcome problems in the community. Community collective action in the form of preventive, curative and promotive actions. Collective preventive action is to distribute masks, hand sanitizers, and spray disinfectants. Collective action in a curative manner, namely by providing social assistance, working on the waqf land and fish ponds, then the visiting neighbor program. Collective action in a promotive manner, namely by disseminating information related to Covid-19 to the public and also by making a handbag made by a cariu student forum from betel leaf. Collective action fosters empathic norms and attitudes in society. Collective action works best when free riding is avoided. The large number of illegal riders made the collective action not maximal. Collective action will also run well if data data and information are well available. Collective action can work well if social capital in the form of a sense of belonging, human values, and empathy grows in individuals.